2016
DOI: 10.1111/1751-7915.12390
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation studies of microbial biofilm communities

Abstract: SummaryAs we look into the future of microbial biofilm research, there is clearly an emerging focus on communities rather than populations. This represents an essential change in direction to more accurately understand how and why microorganisms assemble into communities, as well as the functional implications for such a life style. For example, current research studies shows that communities display emergent properties or functions that are not predicted from the individual single species populations, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…We focused on using a consortium since most environmental processes occur within consortia35, and natural anaerobic methane oxidation involves consortia23.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on using a consortium since most environmental processes occur within consortia35, and natural anaerobic methane oxidation involves consortia23.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial biofilms are three-dimensional sessile structures consisting of bacteria encapsulated within hydrated extracellular polymeric substances (EPS) on a substrate 32 . The exopolysaccharide matrix facilitates irreversible attachment between the biofilm cells and the substrate while simultaneously maintaining intercellular interactions, giving rise to a biofilm architecture specific to a particular substrate and definite bacterial strain 33 .…”
Section: Fundamentals Of Bacterial Growth and Biofilm Formationmentioning
confidence: 99%
“…Bacteria in biofilms are generally embedded in a self‐produced extrapolymeric matrix that mainly consists of polysaccharides, proteins, lipids and nucleic acids. This extracellular matrix is responsible for providing adhesiveness, cohesiveness, stability and three‐dimensional architecture to the biofilm (Abee et al ., ; Domenech et al ., ; Flemming, ; Rice et al ., ).…”
mentioning
confidence: 97%
“…This human health problem is often due to increased resistance of biofilms to different environmental stresses and antimicrobial agents (Davies, ; Van Acker et al ., ; Flemming et al ., ). Importantly, natural biofilms typically consist of multiple bacterial species, and some studies have demonstrated that mixed biofilms exhibit greater resistance to stressors than single‐species biofilms (van der Veen and Abee, ; Lee et al ., ; Rice et al ., ).…”
mentioning
confidence: 97%
See 1 more Smart Citation